Implementing Project-Based Learning With Communicative Approach To Enhance Communication Skills of 8th grade Students - Febriani Hutasuhut; Ahmad Laut Hasibuan; Sutikno; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
This classroom action research aimed to examine the implementation of project-based learning with a communicative approach and the improvement of communication skills among eighth-grade students at MTs Pancasila Tanjung Beringin. The study was motivated by students' low communication abilities, characterized by difficulties in expressing ideas systematically, lack of self-confidence, and the dominance of conventional teaching methods that provided limited opportunities for communication practice. The research was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The subjects were 35 eighth-grade students at MTs Pancasila Tanjung Beringin in the 2025-2026 academic year. Data collection techniques included observation, interviews, pre-test and post-test assessments, and documentation. Data analysis employed quantitative and qualitative descriptive techniques with t-tests to measure the improvement in students' communication skills. The results demonstrated that implementing project-based learning with a communicative approach significantly enhanced students' communication abilities. The class average score increased from 62.43 in the pre-cycle to 72.57 in Cycle I and 81.29 in Cycle II, representing a total improvement of 18.86 points (30.21%). Classical mastery learning increased dramatically from 11.43% (4 students) in the pre-cycle to 34.29% (12 students) in Cycle I and 80.00% (28 students) in Cycle II. All aspects of communication skills showed significant improvement, with self-confidence experiencing the highest increase of 35.70%, followed by idea coherence (33.36%), audience interaction (32.78%), clarity of delivery (28.69%), and language use (28.52%). Active student participation increased from 20% to 97.1%, and students' responses to learning were highly positive with a score of 4.43 on a scale of 5. The study concluded that project-based learning with a communicative approach successfully created a collaborative, communicative, and meaningful learning environment. This model provided extensive opportunities for students to practice communication in authentic contexts, enhanced self-confidence, developed skills in organizing ideas, and facilitated dynamic interactions.